Experimental evaluation of thermophysical properties of oil-based titania nanofluids for medium temperature solar collectors Experimentelle Einschätzung der thermophysikalischen Eigenschaften von ölbasierten Titandioxid-Nanofluiden für Mitteltemperatur-Solarkollektoren - Akhter, J. (Wiley-VCH Verlag, 2020)
Thermal oils are widely used as working fluids in the medium temperature heat transfer applications including concentrating solar thermal collectors. However, the weak thermal characteristics of these oils are major drawbacks in their successful application in the medium-high temperature solar collectors. Fortunately, the emergence of nanotechnology has provided the opportunity to alter thermo-physical properties of base fluids by adding small amount of sub-micron size solid particles possessing better properties. This paper presents an experimental investigation of thermophysical properties of an oil-based nanofluid to be used in the medium temperature solar collector for enhanced thermal energy transport. The colloidal suspensions were prepared by dispersing different weight fractions (0.25 wt., 0.5 wt., 0.75 wt. and 1.0 wt.) of Titania nanoparticles in Therminol-55 oil using two-step method. Shear mixing and high energy ultrasonication was employed to achieve uniform mixing and de-agglomeration of the nanoparticles in order to enhance the stability of the colloidal suspensions. Thermophysical properties of the nanofluids were determined as a function of nanoparticles concentrations in the temperature range of 25Â Â°Câ130Â Â°C. The experimental results demonstrated substantial improvement in thermal conductivity of the nano-oils with an increase in nanoparticles loading which further enhanced at higher temperatures. Dynamic viscosity and effective density displayed a decreasing trend against rising temperature which indicate the effectiveness of these nanofluids for medium temperature heat supply. Nano-oils with superior thermal properties can improve the performance of medium temperature solar thermal collectors. Â© 2020 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim